Component‐Customizable Porous Rare‐Earth‐Based Colloidal Spheres towards Highly Effective Catalysts and Bioimaging Applications. Issue 64 (26th October 2017) - Li, Cheng Chao; Rui, Xianhong; Wei, Weifeng; Chen, Libao; Yu, Yan
Abstract: Multicomponent porous colloidal spheres are of interest because they not only show a combination of the properties associated with all different components, but also usually present synergy effects. However, a combination of different components in a single porous sphere is still greatly challenged due to the different precipitation behaviors of each component. In this work, we have developed a general synthetic route to prepare several categories of porous monodisperse rare‐earth (RE)‐based colloidal spheres with customizable elemental compositions and a uniform element distribution. The two‐step synthetic strategy is based on the integration of coordination chemistry precipitation of RE ions and a subsequent ion‐exchange process, which steers clear of obstacles, such as differences in solubility product constant, that are to be found in traditional co‐precipitation methods. Our approach provides a new mixing mechanism to realize homogeneous distribution of each element within the porous spheres. An array of binary, ternary, and even senary RE colloidal porous spheres with diameters of 500 nm to 700 nm has been successfully synthesized. Taking advantage of their good dispersibility, porosity, and customizable components, these porous RE oxide spheres show excellent catalytic activity for the reduction of 4‐nitrophenol, and promising application in single‐phase multifunctional bioprobes. Abstract : Doing a two‐step with rare earths ! A general synthetic route to prepare several categories of porous monodisperse rare‐earth (RE)‐based colloidal spheres was developed. The two‐step synthetic strategy is based on the integration of coordination chemistry precipitation of RE ions and subsequent ion‐exchange process, which steers clear of obstacle from differences in solubility product constant in traditional co‐precipitation methods.